Interdisciplinary Expert Consensus: the place of original pitavastatin in primary and secondary prevention of cardiovascular diseases - M. G. Bubnova; A. S. Galyavich; M. V. Ezhov; D. M. Aronov; N. N. Vinogradova; G. R. Galstyan; V. S. Gurevich; Yu. A. Karpov; N. A. Koziolova; E. D. Kosmacheva; G. V. Matyushin; I. V. Sergienko; et al. (Российский кардиологический журнал, 2024)
Russian Society of Cardiology, National Atherosclerosis Society, Russian Society of Cardiosomatic Rehabilitation and Secondary Prevention, Russian Association of Endocrinologists